MODEL REGRESI POISSON TERGENERALISASI I - , RAHMALIAH SAHUPALA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Poisson regression model is one of nonlinear regression model that used to analyze count data, where values of mean and variance of response variable are equal, that termed equidispersion. However, quite often founded that count data exhibit substantial variations where the variance of the response variable is either smaller or larger than the mean and it is classified as under- or over-dispersion, respectively. It can cause the parameter estimation are not accurate. One model that can be used to handling that problem is generalized Poisson I regression model.